Human rotavirus virus-like particle vaccines evaluated in a neonatal gnotobiotic pig model of human rotavirus disease. (February 2013) - Azevedo, Marli P; Vlasova, Anastasia N; Saif, Linda J
The authors discuss here rotavirus-like particle vaccines as an alternative approach to oral live-attenuated rotavirus vaccine and their efficacy in a gnotobiotic pig model. Rotavirus virus-like particles (VLPs) were evaluated in different doses, and routes of administration, and combined with live-attenuated virus and adjuvants. A VLP vaccine composed of rotavirus VP2 and VP6 was immunogenic in gnotobiotic pigs when inoculated intranasally; however, this vaccine failed to confer protection. A combination of oral attenuated human rotavirus and intranasal 2/6VLP vaccines conferred immunogenicity, partial protection against a human rotavirus challenge and induced IFN-γ-producing T cells in the ileum of pigs with similar frequencies to human rotavirus infection. Vaccination through a combination of mucosal inductive sites and live-attenuated vaccine combined with VLP vaccines was the most effective regimen, compared with the use of a single route or a single vaccine alone. However, if formulated with neutralizing antigens, VLP vaccines may constitute a better approach in a high maternal antibody scenario.